Micropropagation and Cryopreservation of Genipa americana L. - Souza, Rafaela Ribeiro de (2018)
The genipapo (Genipa americana L.) is a species of high socioeconomic potential due to the various possibilities of use landscaping projects and in the food, pharmaceutical, nanotechnological and logging industries. However, there are several biological, technical and scientific limitations that hinder conservation and discourage its commercial exploitation. Therefore, in vitro cultivation is an alternative to overcome the difficulties imposed by traditional system of genipapo propagation, allowing the multiplication of plants on large scale and using technologies for conservation and cryopreservation. In this context, the aim was to establish a protocol for in vitro regeneration and cryopreservation of Genipa americana seeds. For in vitro regeneration, segments of hypocotyl, root and leaf were obtained from seedling established in vitro. The explants were inoculated in MS medium supplemented with BAP at concentrations of 0.0; 1.12; 2.25 and 3.37 mg L-1. For the acclimatization experiment, plantlets rooted in vitro were transferred to tubes filled with substrate based of vermiculite and peat, and maintained for 14 days in a growth room under with a controlled temperature of 25°C ± 2°C and photon irradiance of 67 μmol m- 2 s-1. Then, they were transferred to greenhouse with 70% shading. At 0, 7, 14, 21 and 28 days after transfer to ex vitro conditions, anatomical, growth and antioxidant enzyme activity analyzes were performed. For cryopreservation, genipap seeds were dehydrated on silica gel (0, 16, 18, 20, 22 and 24 hours), and then cryopreserved in liquid nitrogen (NL) (-196°C). At 40 days of in vitro culture it was observed that the morphogenetic pattern and the regeneration capacity showed a correlations with the explants source (hypocotyl, root and leaf) and BAP concentrations used. MS medium supplemented with 1.12 mg L-1 of BAP proved a higher frequency of shoots in segments hypocotyl, root and leaf. The best results for shoot regeneration rates (80%) and number of regenerated plants per explant (5) were obtained using hypocotyl segments grown on medium MS + 1.12 mg L-1 BAP. At the end of 30 days of acclimatization there was 90% survival of the seedlings. It was also verified that the morphological and physiological alterations such as the emission of new leaves, increase in chlorophyll content, elliptic shape acquisition of the stomata, root survival in vitro and the stimulated activity of antioxidant enzymes ensure the continuity of growth and acclimatization of plants, enabling high survival rate (90%) after acclimatization. As for the cryopreservation, it was observed that removal of seed water content up to 14% (corresponding to 20 hours of dehydration) conferred a higher tolerance to freezing and favored the successful cryopreservation of seeds of Genipa americana, allowing germination (35%) after thawing, high survival rates (100%), with growth and normal establishment of the seedlings after acclimatization. The established methodology, besides being simple and easy to implement, will allow the long-term conservation germplasm of this species.